Rare earth alloying in Cu enhances the C/Cu interfacial wettability for long-lasting copper-based electrical contacts - Bingtian Li; Zhenjie Guan; Yang Li; Ziyao Chen; Weijian Li; Liang Zhen; Wenzhu Shao (Journal of Materials Research and Technology)
C/Cu composites have been widely used in the field of electrical contacts due to their excellent conductivity and anti-ablation properties. However, the poor wettability between C and Cu matrix severely significantly shortens the service life of C/Cu electrical contacts. In this work, we theoretically and experimentally demonstrate that rare earth alloying in Cu matrix enhances the interfacial wettability between C and Cu, leading to the improved electrical contact performance. The wetting angle is reduced from 132° to 46° by the incorporation of La (0.56 wt%) into the Cu matrix, which is attributed to the formation of interfacial LaC2, where the Griffith's separation energy of LaC2/Cu was calculated to be −4.6 J/m2 much lower than those of C/Cu (0.13 J/m2) and C/CuLa (0.06 J/m2). The ablation surface of the electric contact demonstrates that improved wettability can diminish carbon accumulation, thereby reducing the contact resistance from 50 mΩ to 2.2 mΩ after 1000 cycles at 380 V and 60 A, with a reduction of mass loss by 50%.This work reveals the bonding mechanism of C/Cu interface, which paves a way for rational design of C/Cu-based electrical contact materials.